2013
DOI: 10.3892/ijmm.2013.1299
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of DEPTOR induces apoptosis, increases chemosensitivity to doxorubicin and suppresses autophagy in RPMI-8226 human multiple myeloma cells in vitro

Abstract: DEP domain containing mammalian target of rapamycin (mTOR)-interacting protein (DEPTOR) is an mTOR binding protein that is overexpressed in RPMI-8226 human multiple myeloma cells, and plays an important role in maintaining cell survival. However, knowledge on the effects of DEPTOR knockdown on the biological functions of RPMI‑8226 human multiple myeloma cells, is limited. This study aimed to determine the role of DEPTOR in the proliferation, apoptosis and autophagy in these cells and to elucidate the mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Autophagy is a component of stress management system of the cells that is utilized by the cell for removal of defective organelles. Autophagy acts as a survival strategy in established and advanced tumors by maintaining cellular energy levels and enhances chemo-sensitivity of a number of anticancer agents to induce cell death [98][99][100][101][102]. It is not clear yet, how autophagy mediates the pro-survival effects in cancerous cells, the mechanism may involve limiting DNA-damage response-mediated apoptosis or, activation of the high-mobility group box 1 (HMGB1)/ receptor for advanced glycation end products (RAGE) signaling axis [103][104][105].…”
Section: Autophagy Inhibitionmentioning
confidence: 99%
“…Autophagy is a component of stress management system of the cells that is utilized by the cell for removal of defective organelles. Autophagy acts as a survival strategy in established and advanced tumors by maintaining cellular energy levels and enhances chemo-sensitivity of a number of anticancer agents to induce cell death [98][99][100][101][102]. It is not clear yet, how autophagy mediates the pro-survival effects in cancerous cells, the mechanism may involve limiting DNA-damage response-mediated apoptosis or, activation of the high-mobility group box 1 (HMGB1)/ receptor for advanced glycation end products (RAGE) signaling axis [103][104][105].…”
Section: Autophagy Inhibitionmentioning
confidence: 99%
“…PI3K/Akt pathway is frequently hyper-activated in cancer and the activation of its downstream targets is associated with proliferation, differentiation and apoptosis [16]. Indeed, Akt mediates cell survival directly, by inhibiting pro-apoptotic proteins, such as caspase-9 and Bad, and indirectly, by modulating several regulators of cell death including p53 and Nf-KB [17]. In this scenario, high levels of Deptor can sustain cell survival in many cancer cell types.
Fig.
…”
Section: Deptor Biological Functionsmentioning
confidence: 99%
“…In addition, it has been recently demonstrated that Deptor stability is promoted by AMBRA1-mediated Cullin5 inhibition [17]. Moreover, through Deptor accumulation, AMBRA1 establishes a positive feedback loop reinforcing the inhibition of mTOR activity.…”
Section: Deptor Biological Functionsmentioning
confidence: 99%
See 2 more Smart Citations